Design education a strategy to change the perceptions of students Case study of Ciudad Juárez - Rogel Villalba, Erika Anastasia (Springer, Cham, 2020)
Abstract. Effective design can be use as a tool for reduction of crime. This suggests that graphic design interventions that seek to change perceptions could have the potential to reduce violent crime. The inquiry expects the students to work with real problems, obtaining reasons and enriching their ideas to face their social role and responsibility as professional citizens. The objective of this research is to measure the change with respect to the attitudes and discover about effective design in contemporary society.